Study of the electrophysiological mechanisms of anticonvulsant action of the original levetiracetam analog the compound GIZH-290 - T. A. Voronina; S. A. Litvinova; N. A. Gladysheva; А. A. Yakovleva (Фармакокинетика и Фармакодинамика, 2021)
The study used the method of cobalt epilepsy, which allows rats with long-term implanted electrodes in the cortical and subcortical structures of the brain to monitor the dynamics of the formation and migration of Epi-foci for a long time. It was found that in the control at the 1st stage of development of the Epi system, Epi activity is most pronounced in the electrocorticograms of the ipsilateral cortex, and at the 2nd, stable stage of development of the Epi system – in the contralateral cortex and subcortical structures. The compound GIZH-290 (the original structural analogue of levetiracetam) reduces the number of Epi discharges and their duration at the 2nd, stable stage of the development of the Epi system. The target structure of the GIZH – 290 compound was the hippocampus. The compound GIZH -290 selectively statistically significantly reduces both the number and duration of Epi – discharges only in the hippocampus and does not affect the foci of epileptic activity in the ipsi-and contralateral cortex and hypothalamus.